Variable Bit Rate Video Workload Modeling for Mobile Broadband Wireless Networks - Ebadinezhad, Sahar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Achieving high throughput, low packet delay, and fair bandwidth sharing are significant issues in resource allocation schemes for mobile broadband wireless networks. With the advent of the fourth generation (4G) wireless systems such as Long Term Evolution (LTE) and WiMAX, resource allocation schemes must be tailored for orthogonal frequency division multiple accesses (OFDMA). Downlink OFDMA can be modeled as a multi-channel, multi-queue system. In order to be able to evaluate resource allocation algorithms over such systems, efficient network traffic models are necessary. The majority of the studies on scheduling are based only on simulations preventing wireless equipment vendors from obtaining quick insights into the behavior of schedulers. Only a subset of the existing work employs analytical queuing models. This thesis aims to use both model-based and simulation-based scheduling studies for 4G wireless systems. Variable bit rate (VBR) video traffic is used for generating workload for the downlink of a 4G-like system. Four scheduling algorithms, round robin (RR), opportunistic (OP), maximum weight (MW) and server-side greedy (SSG), are then investigated and their performances are compared for video over 4G. The results of the analysis show that RR is highly unstable compared to OP, MW, and SSG. In terms of the length of the user queues, the best performance belongs to SSG having small user queue lengths. Keywords: 4G, OFDMA, scheduling, video traffic models

ÖZ: Gezgin geniş bantlı telsiz ağlar için kaynak atama yöntemlerinde yüksek hız, az gecikme ve adil kaynak paylaşımı önemli konulardır. LTE ve WiMAX gibi dördüncü kuşak (4G) telsiz iletişim sistemlerinde kaynak atama yöntemleri dik frekans bölmeli çoklu erişime (OFDMA) uygun yapılmalıdır. Aşağı bağlantı OFDMA çok kuyruklu çok kanallı sistemler olarak modellenebilmektedir. Bu tür sistemlerde, kaynak atama algoritmalarını değerlendirmek için etkin ağ trafik modelleri gerekmektedir. Sıralayıcılarla ilgili birçok çalışma sadece benzetimlere dayanmakta ve telsiz sistem sağlayıcılarının sıralayıcıların çalışmasına dair hızlı bir öngörü oluşturmasına olanak vermemektedir. Sadece bir kısım çalışma analitik kuyruklama modellerine dayanmaktadır. Bu tezde, benzetim ve model bazlı sıralayıcı çalışmalarının beraber kullanılması amaçlanmıştır. Değişken video hızlı (VBR) video trafik modeli kullanılıp 4G sistem modelleri için trafik üretilmiştir. Dört sıralayıcı algoritması, değişmez zaman paylaşımı (RR), fırsatçı (OP), en büyük ağırlık (MW) and sunucu-taraflı aç gözlü (SSG), değerlendirilip video trafiği ile 4G üzerinde performansları karşılaştırılmıştır. Analiz sonuçlarına göre RR, OP, MW ve SSG’ye göre oldukça kararsızdır. Kuyruk uzunluğu dikkate alındığında ise, en iyi kısa kuyruk performansını SSG göstermektedir. Keywords: 4G, OFDMA, sıralama, video trafık modelleri
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2014. Supervisor: Assoc. Prof. Dr. Doğu Arifler.
Keywords: Computer Engineering; Wireless communication systems; Wireless Technology - Computer Communication Networks; 4G; OFDMA; scheduling; video traffic models